Visual acuity increase in meridional amblyopia by exercises with moving gratings as compared to stationary gratings. (3rd April 2022) - Kämpf, Uwe; Rychkova, Svetlana; Lehnert, Ron; Heim, Evelyn; Muchamedjarow, Felix
ABSTRACT: The aim of the present work was to investigate the effect of a novel therapy based on pleoptic exercises combined with standard occlusion in patients with meridional amblyopia. The exercising system itself, termed focal ambient visual acuity stimulation (FAVAS), consists of sinusoidally modulated circular gratings, which were implemented as a background pattern in computer games binding the children's attention. For the assessment of therapeutic effects, we tested for the development of best-corrected visual acuity (BCVA) in patients trained with a gaming field background of moving gratings (Moving) compared to patients treated with stationary gratings (Stationary). Patients with amblyopia (caused by strabismus, refraction, or both) and astigmatism were randomly allocated to two groups, all of whom received a standard occlusion regimen. In combination with occlusion, using a crossover design, the first group (Moving-Stationary group) was alternately exercised for 10 days with a series of Moving followed by 10 days with Stationary and the second group (Stationary-Moving group) vice versa. The treatment-dependent training effect on BCVA was measured with respect to the alignment of the least vs. the most ametropic meridian in both groups. BCVA was examined using a meridionally direction-sensitive visual test inventory, and we estimated the monocular BCVA in all patients along four meridians: 0°, 45°, 90°, and 135° before and after Moving as compared to Stationary treatments. The Moving-Stationary group consisted of 17 children (34 eyes) aged 10 to 13 (average 11.6 ± 0.3) years. The Stationary-Moving group consisted of 20 children (40 eyes) aged 9 to 14 (average 12.5 ± 0.4). In both groups, visual acuity increased significantly only with Moving combined with occlusion. Thereby, the visual acuity (logMAR) along different meridians showed a statistically significant improvement induced by Moving if testing was coincident with alignment of the directional optical characters close to the most ametropic meridian in the Moving-Stationary group (0.73 ± 0.32 to 0.41 ± 0.22, p  < 0.01) and also in the Stationary-Moving group (0.48 ± 0.27 to 0.33 ± 0.18, p  < 0.01). Significant improvement was also induced by Moving if tested in alignment with the perpendicular orientation close to the least ametropic meridian, although with a smaller amount, in the Moving-Stationary group (0.49 ± 0.23 to 0.37 ± 0.21, p  < 0.01) as well as in the Stationary-Moving group (0.33 ± 0.18 to 0.28 ± 0.16, p  < 0.01). After Stationary combined with occlusion, however, there was no statistically significant improvement, regardless of the meridian. Visual training of patients with meridional amblyopia by a series of online exercises using attention-binding computer games which contained moving gratings as a background stimulus (Moving) resulted in a statistically significant improvement in visual acuity in the most refractive meridian, and to a lesser extent, in the least refractive meridian. No statistically significant improvement was achieved after the respective exercising series in the sham condition with stationary gratings (Stationary).